FTIR-ATR spectroscopy to identify and quantify the SBS in modified bitumen - Škulteckė, Judita; Bitarytė, Simona; Liubinas, Karolis (International Conference “Environmental Engineering”, 2023)
The aim of this paper is to demonstrate that the Fourier transform infrared (FTIR) spectroscopy with attenuated total reflexion (ATR) technique is a rapid and suitable method for identifying and preliminary quantifying the amount of styrene-butadiene–styrene (SBS). For this purpose, unmodified and modified binders were tested with FTIR-ATR spectroscopy. Both the laboratory modified binders and modified bitumen existing in the market were analysed. In addition to this, multi stress creep recovery (MSCR) test was used to demonstrate the importance of polymers and the dependency of results on the amount of SBS. The research results showed that FTIR-ATR spectroscopy is a suitable method to identify and preliminary quantify the amount of SBS in modified bitumen and that the higher amount of SBS, the better the performance of bitumen is.